RAINBIO: a mega-database of tropical African vascular plants distributions - Dauby, Gilles; Zaiss, Rainer; Blach-Overgaard, Anne; Catarino, Luís; Damen, Theo; Deblauwe, Vincent; Dessein, Steven; Dransfield, John; Droissart, Vincent; Duarte, Maria Cristina; Engledow, Henry; Fadeur, Geoffrey; et al. (PhytoKeys, 2016)
The tropical vegetation of Africa is characterized by high levels of species diversity but is undergoing important shifts in response to ongoing climate change and increasing anthropogenic pressures. Although our knowledge of plant species distribution patterns in the African tropics has been improving over the years, it remains limited. Here we present RAINBIO, a unique comprehensive mega-database of georeferenced records for vascular plants in continental tropical Africa. The geographic focus of the database is the region south of the Sahel and north of Southern Africa, and the majority of data originate from tropical forest regions. RAINBIO is a compilation of 13 datasets either publicly available or personal ones. Numerous in depth data quality checks, automatic and manual via several African flora experts, were undertaken for georeferencing, standardization of taxonomic names and identification and merging of duplicated records. The resulting RAINBIO data allows exploration and extraction of distribution data for 25,356 native tropical African vascular plant species, which represents ca. 89% of all known plant species in the area of interest. Habit information is also provided for 91% of these species.
Keywords: taxonomic backbone; tropical forests; biodiversity assessment; cultivated species; georeferencing; digitization; Herbarium specimens; native species; habit